2019
DOI: 10.3390/ijerph16091526
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin—Microbial Degradation and Interactions with Environmental Bacterial Strains

Abstract: The continuous exposure of living organisms and microorganisms to antibiotics that have increasingly been found in various environmental compartments may be perilous. One group of antibacterial agents that have an environmental impact that has been very scarcely studied is nitrofuran derivatives. Their representative is nitrofurantoin (NFT)—a synthetic, broad-spectrum antibiotic that is often overdosed. The main aims of the study were to: (a) isolate and characterize new microbial strains that are able to grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Similar observations were made in our study. Moreover, our previous research showed that the presence of another 5-nitrofuran derivative, nitrofurantoin, contributed to a decrease in the cell metabolic activity of newly isolated environmental bacterial strains [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations were made in our study. Moreover, our previous research showed that the presence of another 5-nitrofuran derivative, nitrofurantoin, contributed to a decrease in the cell metabolic activity of newly isolated environmental bacterial strains [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The issues of bioavailability and changes in cell surface properties induced by contact with nitrofuran-derived antibiotics have not yet been analyzed in detail. We noticed in our previous research that contact with nitrofurantoin led to a decrease in Congo red adsorption on Sphingomonas paucimobilis and Rhizobium radiobacter [ 27 ]. However, in the case of Sphingobacterium thalpophilum cells, an increase in the tested parameter was noticed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated sludge was collected aseptically from the urban wastewater treatment plant in Poland (52°25′53.1″ N, 16°57′31.8″ E) and used for bacterial strains isolation. The isolation process was carried out as described previously with the mixture of Fl, Ep, Cb and Cl used as a selective agent [ 55 ]. The isolated bacterial strain that was able to grow in the presence of azole derivatives was identified using biochemical (Vitek ® 2 system, bioMérieux, Warsaw, Poland) and molecular techniques as O. anthropi AspCl 2.2 (GenBank: MK503652.1) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next, a loop full of cells was introduced to a nutrient broth and the bacteria were allowed to grow overnight at 30 °C with shaking (120 rpm, KS 400 ic control, IKA Werke, GmbH, Staufen, Germany). The bacterial suspension obtained was washed three times (4000× g , 10 min, Centrifuge 5910R, Eppendorf, Germany) with sterile mineral salt medium (MSM, composition as in [ 55 ]). In the final stage, the cell pellet was resuspended in MSM to adjust optical density to 1.0 ± 0.1 at λ = 600 nm (Multiskan Sky, Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%